2022
DOI: 10.1021/acsapm.2c00803
|View full text |Cite
|
Sign up to set email alerts
|

Unclonable Features via Electrospraying of Bulk Polymers

Abstract: The ability to encode unclonable information using low-cost materials and processes is of significant interest for anti-counterfeiting and information security applications. In this study, we present a versatile approach based on electrospraying of polymer solutions to generate randomly positioned complex features as a form of physically unclonable function (PUF). The key advantage of this approach is that readily available low-cost bulk polymeric materials can form small and complex features using a simple pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 66 publications
0
35
0
Order By: Relevance
“…[20][21][22] Recently, randomly distributed ESNFs or natural micro/nanofibers have rapidly developed as a novel candidate of PUFs. [23][24][25][26] Feng et al fabricated plasmonic anti-counterfeiting labels based on surface-enhanced Raman spectroscopy of the Au@SiO 2 -embedded ESNFs. 23 Tas -cıog ˘lu et al produced unique security patterns by electrospinning and verified the random patterns using an image processing method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Recently, randomly distributed ESNFs or natural micro/nanofibers have rapidly developed as a novel candidate of PUFs. [23][24][25][26] Feng et al fabricated plasmonic anti-counterfeiting labels based on surface-enhanced Raman spectroscopy of the Au@SiO 2 -embedded ESNFs. 23 Tas -cıog ˘lu et al produced unique security patterns by electrospinning and verified the random patterns using an image processing method.…”
Section: Introductionmentioning
confidence: 99%
“…24 The randomness of electrospun nanofibers (ESNFs) arises from the stretching, elongation and deformation of droplets within Taylor cones during the electrohydrodynamic process, resulting in linear segment perturbations, unstable bending and small coils. 22,25 Then, the strong PUF based on these kaleidoscopic morphologies is believed to be unpredictable and effective against machine learning attacks. 27 Another concern is the conciseness of fingerprints.…”
Section: Introductionmentioning
confidence: 99%
“…Physically unclonable functions (PUFs) have recently attracted increasing attention for authentication and anticounterfeiting applications because of their unpredictable and unreproducible nature. The underlying concept of PUFs is the use of physical systems with random responses as cryptographic primitives. , Various research efforts have been made to create PUF-based security tags that are completely immune to forgery and cloning. High encoding capacities have been attained by maximizing the spatial randomness of tag components and using multiplex encoding strategies. Cost-effective and widely applicable fabrication processes should be further developed to realize the extensive use of such PUF-based security tags in various commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Esidir et al reported that electro-spraying could be used to create polymer mats with unique morphologies and properties that could be used as a basis for anticounterfeiting. [13] A paper by Wang et. al.…”
Section: Introductionmentioning
confidence: 99%